Faunal diversity in Malaysian mangroves - Sasekumar, A.; Chong, V.C. (1998)
Malaysian mangroves harbour a high diversity of benthic invertebrates, including poly- chaetes, gastropods, brachyurans, and sipunculids. In three sites at different points in the forest harvest cycle at Matang, the density and biomass of epifaunal taxa was found to be greatest in mature Rhizophora apiculata Lamk. forest, intermediate in a 15-year old stand, and lowest in recently cleared forest. The pattern in infaunal taxa was found to be different, with the greatest density and biomass in the recently cleared site. A number of diversity indices highlight the low diversity of epifaunal taxa in the recently cleared site, perhaps a consequence of the drier substrate surface in the absence of a tree canopy.